Clinical profile and outcome of carbapenem-resistant gram negative bacteremia in children with cancer in pediatric intensive care unit of a resource-limited country - Uzair Ali Memon; Abdul Rahim Ahmed; Muhammad Khalid; Karima Qadir; Naeem Jabbar; Samina Junejo; Anwar ul Haque (Elsevier, 2020)
Objective: The prevalence of Carbapenem-Resistant Gram Negative Blood Stream Infection (CRGN-BSI) is increasing worldwide. However, there is a paucity of data in a vulnerable population "Children with cancer". The objective of this study is to describe the clinical profile and outcome of children with cancer admitted in PICU with CRGN-BSI. Methods: We retrospectively reviewed medical record of all children with cancer admitted in PICU who had CRGN-BSI from September 2017 to August 2019. Isolates with meropenem MIC ≤19 mg/dl were considered as Carbapenem Resistant. Responder was defined as negative blood culture in 5 days. Clinical profile and outcomes were obtained. Descriptive statistics were applied. Results: Out of 1234 PICU admissions, 54 children with cancer developed CRGN-BSI (0.3%). The mean age of CRGN-BSI was 6.97 ± 4 years. 67% (n = 36) of these were male and 54% (n = 29) were malnourished. The primary diagnosis was hematological malignancy in 80% (n = 43) and 76% of the children used ICU therapies (mechanical ventilation [n = 14, 26%] and vasoactive inotropic support [n = 27, 50%]). All of them were neutropenic on admission and 98% patients received blood products. Pending blood culture results, 50% (n = 27) of the patients were started on meropenem. E-coli (n = 30, 56%) and Kelbseilla species (n = 14, 26%) were the most common isolates in our cohort and 46% (n = 25) of the patients were the responders. 18% (n = 10) were community acquired infection and 82% (n = 44) were health-care associated infections. The case-fatality rate was 35% (n = 19). Age, gender, nutritional status and empirical meropenem were not associated with mortality. Conclusion: CRGN-BSI in children with underlying malignancy is a serious illness with high mortality. No single factor could determine the mortality in our study. We suggest study with larger sample size, early blood culture testing and rational use of Carbapenem.